2018
DOI: 10.1007/s10620-018-5122-4
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Composition Before and After Use of Proton Pump Inhibitors

Abstract: BackgroundRecently, problems associated with proton pump inhibitor (PPI) use have begun to surface. PPIs influence the gut microbiota; therefore, PPI use may increase the risk of enteric infections and cause bacterial translocation. In this study, we investigated fecal microbiota composition, fecal organic acid concentrations and pH, and gut bacteria in the blood of the same patients before and after PPI use.MethodsTwenty patients with reflux esophagitis based on endoscopic examination received 8 weeks of trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
73
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 60 publications
6
73
1
2
Order By: Relevance
“…These results have been replicated in subsequent studies 41,42 . To the best of our knowledge, this is the first study which has assessed the effect of PPI on the small intestinal bacterial load utilising qPCR, with the majority of previous studies focusing on stool samples 43‐45 and/or samples from the oral cavity 40,46 . Thus, our data provide further evidence that PPI therapy is associated with a small intestinal “dysbiosis” but expands this concept to variations in bacterial load on tissue.…”
Section: Discussionsupporting
confidence: 62%
“…These results have been replicated in subsequent studies 41,42 . To the best of our knowledge, this is the first study which has assessed the effect of PPI on the small intestinal bacterial load utilising qPCR, with the majority of previous studies focusing on stool samples 43‐45 and/or samples from the oral cavity 40,46 . Thus, our data provide further evidence that PPI therapy is associated with a small intestinal “dysbiosis” but expands this concept to variations in bacterial load on tissue.…”
Section: Discussionsupporting
confidence: 62%
“…These studies focused on the concomitant use of these two drugs and showed no influence of PPIs on the pharmacokinetics of NSAIDs [ 45 , 46 ]. However, PPI use might increase the risk of an imbalance in gut microbiota composition, even 8 weeks after PPI treatment [ 47 , 48 ]. This change in microbiota composition has been shown to exacerbate NSAID side effects [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…PPIs decrease the acidity in the stomach by inhibition of the H + /K + -ATPase enzyme in the parietal cells of the gastric glands. As a consequence, the pH of the proximal intestine is increased [29,32], which can affect the gut microbiome [33,34]. The use of PPIs has also been associated with a decreased absorption of vitamin B 12 , magnesium, calcium, iron, vitamin C, β-carotene, and zinc, which is at least in part a direct consequence of their reduced release from the food matrix and (or) effects on the absorption process [29,[35][36][37][38] At the clinical level, PPI use has been reported as a variable of importance, after gait speed, oxidative stress, and depression, in the prediction of muscle mass and function loss in aging (sarcopenia) [39].…”
Section: Adverse Effects Of Long Term Use Of Ppismentioning
confidence: 99%
“…To conclude, although generally considered safe, long-term use of PPIs could ultimately lead to deficiencies in several vitamins and minerals [36,37,43]. Furthermore, the changed pH can affect the gut microbiome [33,34], and finally, it can result in the presence of myopathy, which might affect muscle function and mass [39].…”
Section: Adverse Effects Of Long Term Use Of Ppismentioning
confidence: 99%